Knowledge to Practice in Developmental Coordination Disorder: Utility of an Evidence-Based Online Module for Physical Therapists. (1st May 2015) - Rivard, Lisa; Camden, Chantal; Pollock, Nancy; Missiuna, Cheryl
ABSTRACT Aims: Developmental coordination disorder (DCD) is a chronic condition with potential negative health consequences. Therapists working with children with DCD need access to tailored, synthesized, evidence-based information; however a knowledge-to-practice gap exists. The aim of this study was to develop and evaluate the utility of an evidence-based online DCD module tailored to physical therapists' (PTs) needs. Methods: Guided by the Knowledge to Action framework, we interviewed PTs working with children with DCD (n = 9) to identify their information needs. Their recommendations, along with synthesized DCD research evidence, informed module development. These PTs as well as others (n = 50) evaluated the module's usefulness. Results: The module incorporated important content areas including: (1) identification; (2) planning interventions and goals; (3) evidence-based practice; (4) management; and (5) resources. Case scenarios, clinical applications, interactive media, links to resources, and interactive learning opportunities were also embedded. PTs perceived the module to be comprehensive and useful and provided feedback to improve module navigation. Conclusions: Involving end-users throughout the development and evaluation of an online PT DCD module contributed to its relevance, applicability, and utility. It will be important to evaluate whether use of this module improves the quality of services provided by PTs.